Beyond al-Qaeda: Part 1, The Global Jihadist Movement - Rabasa, Angel (RAND Corporation, 2006)
Examines al-QaedaÂ•s evolution and the emergence of the broader global jihadist movement-groups affiliated, associated, or inspired by al-Qaeda-and the threat that they pose to the United States and U.S. allies and interests. The authors conclude by setting out a four-pronged strategy to counter the jihadist threat.